RETRACTED: An empirical analysis of FDI and institutional quality on environmental quality and economic growth, evidence from the panel of asian oil-producing and non-oil-producing economies - Ali, Arshad (Frontiers in Environmental Science, 2023)
This study applies the augmented mean group (AMG) estimation technique to investigate whether institutional quality and FDI contribute to economic growth and environmental quality in emerging Asian oil-producing and non-oil-producing countries during the period 1975–2020. The estimation of AMG strategy indicates that for every 1% increase in FDI, institutional quality and carbon emissions can significantly boost economic growth by 0.882%, 0.659%, and 0.605%, respectively. Likewise, trade liberalization, transport infrastructure and urbanization can significantly boost economic growth. Long-term variable elasticity coefficients based on carbon emissions model suggest that FDI can stimulate carbon emissions, thereby validating the Pollution Heaven Hypothesis (PHH) in selected panel of countries. Institutional quality has a significant negative impact on carbon emissions, while GDP, trade openness, urbanization, and investment in transport infrastructure contribute significantly to carbon dioxide emissions. Country wise estimates of the AMG strategy show that the institutional quality of oil-producing countries has no significant impact on economic growth, but does boost economic growth in non-oil producing countries. The quality of institutions in both non-oil and oil-producing countries can significantly reduce carbon emissions. FDI stimulates economic growth in oil-producing countries compared to non-oil-producing countries. However, FDI contributes significantly to both oil and non-oil-producing CO2 emissions, thus validating PHH. Controlling factors such as economic growth increase significantly to CO2 emissions in oil-producing countries, while, CO2 emissions from petro-states stimulate more to economic growth than non-petroleum states. The impact of trade liberalization on economic growth is significantly positive in both oil and non-oil-producing countries, but the contribution of non-oil-producing economies is higher than that of oil-producing countries. Compared with non-oil producing countries, trade liberalization in oil-producing countries contributes more to carbon emissions. Investment in transportation infrastructure significantly boosted economic growth in both oil and non-oil producing countries, but oil producing countries contributed more than non-oil producing countries. A range of policy proposals were discussed to achieve economic and environmental sustainability.